2022
DOI: 10.1109/tcsvt.2022.3182793
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the Low Complexity Enhancement Video Coding (LCEVC) Standard

Abstract: The Low Complexity Enhancement Video Coding (LCEVC) specification is a recent standard approved by the ISO/IEC JTC 1/SC 29/WG04 (MPEG) Video Coding. The main goal of LCEVC is to provide a standalone toolset for the enhancement of any other existing codec. It works on top of other coding schemes, resulting in a multi-layer video coding technology, but unlike existing scalable video codecs, adds enhancement layers completely independent from the base video. The LCEVC technology takes as input the decoded video a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Due to its effective reduction in video encoding complexity, various studies have demonstrated significant bitrate and encoding time gains compared to original encoders [132]. Ferrara et al [131] validated the benefits of LCEVC through experimentation, demonstrating a significant decrease in the overall complexity of the end-to-end process.…”
Section: Enhanced Video Codingmentioning
confidence: 99%
“…Due to its effective reduction in video encoding complexity, various studies have demonstrated significant bitrate and encoding time gains compared to original encoders [132]. Ferrara et al [131] validated the benefits of LCEVC through experimentation, demonstrating a significant decrease in the overall complexity of the end-to-end process.…”
Section: Enhanced Video Codingmentioning
confidence: 99%
“…Due to the potential to enhance video delivery efficiency and mobile users' QoE, layered SVC streaming has been widely investigated. Literature [13] gives a detailed survey on the LCEVC technology. In [14], the authors propose an adaptive policy iteration algorithm to improve the QoS in wireless scalable video multicast.…”
Section: A Related Workmentioning
confidence: 99%
“…In [16] the authors provide a description of the LCEVC specification and an analysis of the individual coding tools comprised in LCEVC, highlighting the low complexity and the innovative aspects of such tools. If [16] is an overview of LCEVC, the current paper provides a synthesis of the methodologies used and the results obtained in the LCEVC verification tests.…”
Section: Introductionmentioning
confidence: 99%
“…In [16] the authors provide a description of the LCEVC specification and an analysis of the individual coding tools comprised in LCEVC, highlighting the low complexity and the innovative aspects of such tools. If [16] is an overview of LCEVC, the current paper provides a synthesis of the methodologies used and the results obtained in the LCEVC verification tests. As noted above, the verification test is the final phase of the development of an MPEG Video coding standard, since it is crucial to confirm the performances of the new video coding technology with respect to the objectives set forth at the beginning of the standard development activity.…”
Section: Introductionmentioning
confidence: 99%